The patient’s sex determines the hemodynamic profile in patients with Cushing disease - Jurek, Agnieszka; Krzesiński, Paweł; Uziębło-Życzkowska, Beata; Witek, Przemysław; Zieliński, Grzegorz; Kazimierczak, Anna; Wierzbowski, Robert; Banak, Małgorzata; Gielerak, Grzegorz (Frontiers in Endocrinology, 2023)
Background Cushing disease (CD) may lead to accelerated cardiovascular remodeling and increased mortality. There are suspected differences in the mechanism of cardiovascular dysfunction between males and females with CD. The purpose of this study was to assess the effect of patient sex on the hemodynamic profile assessed via impedance cardiography and echocardiography in patients newly diagnosed with CD. Material and methods The 54 patients newly diagnosed with CD (mean age 41 years; 77.8% of females) who were included in this prospective clinical study underwent impedance cardiography to assess specific parameters (including systemic vascular resistance index [SVRI], total arterial compliance index [TACI], Heather index [HI], stroke index [SI], cardiac index [CI], velocity index [VI], and acceleration index [ACI]) and transthoracic echocardiography to assess heart chamber diameters and left ventricular systolic and diastolic function. Results Males with CD exhibited higher afterload, with higher SVRI (3,169.3 ± 731.8 vs. 2,339.3 ± 640.8 dyn*s*cm-5*m² in males and females, respectively; p=0.002), lower TACI (0.80 ± 0.30 vs. 1.09 ± 0.30 mL/mmHg*m2; p=0.008), and lower hemodynamic parameters of left ventricular function, with lower HI (9.46 ± 2.86 vs. 14.1 ± 5.06 Ohm/s2; p=0.0007), lower VI (35.1 ± 11.9 vs. 44.9 ± 13.1 1*1000-1*s-1; p=0.009), lower SI (36.5 ± 11.7 vs. 43.6 ± 9.57 mL/m2; p=0.04), lower CI (2.36 ± 0.46 vs. 3.17 ± 0.76 mL*m-2*min-1; p=0.0009), and lower ACI (50.4 ± 19.8 vs. 73.6 ± 25.0 1/100/s2; p=0.006). There were no significant differences between the sexes in left ventricular systolic or diastolic function assessed by echocardiography. Conclusion In comparison with females with CD, males with CD have a less favorable hemodynamic profile, with higher afterload and worse left ventricular function. Sex differences in cardiovascular system function should be taken into consideration in designing personalized diagnostic and therapeutic management of patients with CD.